2016
DOI: 10.1158/0008-5472.can-15-2946
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Differentially Regulates Distinct Breast Cancer Stem-like Cells in Murine Models via EGFR/Stat3 and Tgfβ/Smad Signaling

Abstract: Cancer stem-like cells contribute to tumor heterogeneity and have been implicated in disease relapse and drug resistance. Here we show the co-existence of distinct breast cancer stem-like cells (BCSC) as identified by ALDH+ and CD29hiCD61+ markers, respectively, in murine models of breast cancer. While both BCSC exhibit enhanced tumor initiating potential, CD29hiCD61+ BCSC displayed increased invasive abilities and higher expression of epithelial to mesenchymal (EMT) and mammary stem cell-associated genes, whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
103
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 52 publications
6
103
0
Order By: Relevance
“…In breast cancers, although tumor cells are organized in a hierarchical manner where CSCs exhibit features of stem/progenitor cells [11], there is plasticity which allows the acquisition of CSC traits by bulk tumor cells [12]. Accordingly, it is conceivable that dynamic conversions as a result of differentiation and plasticity can give rise to tumors with cells that correspond to distinct differentiation states of the normal mammary gland hierarchy [13, 14]. Due to the plasticity of tumor cells, therapeutic strategies will need to consider all the cell types within the hierarchical structure of the tumor and not just CSCs alone, since re-emerging CSC populations can arise from bulk tumor cells [15, 16].…”
Section: Cancer Stem Cells: a Source Of Non-genetic Heterogeneitymentioning
confidence: 99%
See 3 more Smart Citations
“…In breast cancers, although tumor cells are organized in a hierarchical manner where CSCs exhibit features of stem/progenitor cells [11], there is plasticity which allows the acquisition of CSC traits by bulk tumor cells [12]. Accordingly, it is conceivable that dynamic conversions as a result of differentiation and plasticity can give rise to tumors with cells that correspond to distinct differentiation states of the normal mammary gland hierarchy [13, 14]. Due to the plasticity of tumor cells, therapeutic strategies will need to consider all the cell types within the hierarchical structure of the tumor and not just CSCs alone, since re-emerging CSC populations can arise from bulk tumor cells [15, 16].…”
Section: Cancer Stem Cells: a Source Of Non-genetic Heterogeneitymentioning
confidence: 99%
“…A continuum of differentiation states that are reflective of the normal mammary hierarchy (Figure 1) is plausible and would result in hierarchical heterogeneity within breast tumors [11, 14]. With regards to this, multiple independent studies have observed the presence of minimally overlapping distinct CSC populations within tumors based on the expression of established CSC markers such as CD44 hi /CD24 − , ALDH + , CD133 + or CD29 hi /CD61 + [13, 1719]. The heterogeneity of the observed CSC populations could be a representation of the diversity in normal mammary stem/progenitor cells that are spatially and temporally regulated [2031].…”
Section: Cancer Stem Cells: a Source Of Non-genetic Heterogeneitymentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptional factors such as Twist1, ZEB2, Snail and FOXC2 can directly or indirectly trigger the EMT [9]. However, the molecular mechanisms by which EMT and MET occur during cancer progression are still unclear [10]. …”
Section: Introductionmentioning
confidence: 99%